Factors associated with the iron nutritional status of Brazilian children aged 4 to 7 years - ANDRÉ, Hercílio Paulino (2023)
ObjectiveTo evaluate factors associated with the iron nutritional status of Brazilian children aged 4 to 7 years in the city of Viçosa, Minas Gerais state, Brazil. MethodsThis is a cross-sectional study of 357 children aged 4-7 years who had been followed-up up for during their first six months of life by the Breastfeeding Support Program. Socioeconomic and demographic characteristics, feeding practices, nutritional status (height-for-age and body mass index-for-age), and serum ferritin and hemoglobin concentrations were evaluated. Multiple linear regression analysis was carried out to evaluate factors independently associated with iron nutritional status (hemoglobin and ferritin), considering α=0.05 as the significance level. ResultsThe prevalence of anemia and iron deficiency was (34) 9.52% and (11) 11.00%, respectively. The factors independently associated with anemia were younger child age, low maternal education, low height-for-age Z-scores, and children of single and separated mothers or widows. Iron deficiency was associated with child younger age and consumption of chocolates and chocolate flavored milk. ConclusionThe results obtained allow us to conclude that anemia among children 4-7 years of age is a public health problem in the city of Viçosa, Minas Gerais. Therefore, there is a need for intervention measures targeting children in this age group. These measures can be implemented through food and nutritional education by encouraging the consumption of iron-rich foods.